Museums in Ghana: Visitor Education, Experiences and Satisfaction - Samuel Nortey; Kwasi Amoako-Hene; Edwin Kwesi Bodjawah (Graduate School of Institut Seni Indonesia Yogyakarta, 2022)
This study looked at visitor experience and satisfaction on museum education in Ghana. Visiting and studying nine museums under the Ghana Museums and Monument Board (GMMB) and using both qualitative and quantitative approaches, the study revealed that visitor experiences, satisfaction, and education within museums under GMMB are unsatisfactory. There are issues with teaching methods, the state of exhibits and exhibition styles and a challenge of low possibility for visitor revisit. There is the need to commit resources to strengthen museums and the introduction of activities which would serve as grounds for museum learning. A strong engagement of visitor education in a positive, socio-cultural, and conducive learning atmosphere is very much expedient. The paper recommended a framework of diversity and inclusion that would support the creation of meaningful visitor experiences and enhance museum education in Ghana. Museum di Ghana: Pendidikan, Pengalaman, dan Kepuasan Pengunjung Abstrak Studi ini melihat pengalaman dan kepuasan pengunjung terhadap pendidikan museum di Ghana. Mengunjungi dan mempelajari sembilan museum di bawah Dewan Museum dan Monumen Ghana (GMMB) dan menggunakan pendekatan kualitatif dan kuantitatif, studi ini mengungkapkan bahwa pengalaman pengunjung, kepuasan dan pendidikan di dalam museum di bawah GMMB tidak memuaskan. Ada masalah dengan metode pengajaran, keadaan pameran dan gaya pameran dan tantangan kemungkinan rendah untuk kunjungan kembali pengunjung. Ada kebutuhan untuk menyediakan sumber daya untuk memperkuat museum dan pengenalan kegiatan yang akan berfungsi sebagai landasan untuk pembelajaran museum. Keterlibatan yang kuat dari pendidikan pengunjung dalam suasana belajar yang positif, sosial budaya dan kondusif sangat diperlukan. Artikel ini merekomendasikan kerangka keragaman dan inklusi yang akan mendukung terciptanya pengalaman pengunjung yang bermakna dan meningkatkan edukasi museum di Ghana.